Practical safety management for small or medium enterprises - Ferjenčík, Miloš (My University, 2020)
The article is intended for those who are not safety professionals but are responsible for safety management in a small or medium enterprise (SME) of the process industry. It assumes that a SME is loosely coupled and of low complexity and has a small number of major hazards present in it. The article describes Elementary Safety Management (ESM) as a combination of activities that maintain openness to safety impulses with Elementary Risk Control (ERC). ERC uses four milestones and three rules to get to the necessary and sufficient selection of control measures, which will achieve an acceptable level of risk. To make the ESM scheme as simple as possible, the term causal event is used, which is derived from the term causal factor. Practical Safety Management (PrSM) adds to the ESM the knowledge and skills that a person, who is supposed to design and implement a safety management system, needs. The PrSM procedure is developed to identify optimum controls. The procedure recognizes the unavoidable role of commitment to safety, respects the role of hazard identification, and integrates prospective and retrospective analyses and current knowledge of safety management systems. Examples of application of the procedure are given in the article..
Praktické řízení bezpečnosti pro malé nebo střední podniky
Keywords: safety management; small or medium enterprise; causal event; control; safety trivium; řízení bezpečnosti; malý nebo střední podnik; příčinná událost; ovládání; bezpečnostní trivium